2017
DOI: 10.14639/0392-100x-1252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of extrapulmonary head and neck tuberculosis in an urban setting

Abstract: La tubercolosi del distretto testa collo è abbastanza comune nei paesi endemici, ma è ancora sottostimata a causa della presentazione clinica assai variabile e a causa dei differenti siti coinvolti. Pertanto, gli obiettivi di questo studio sono stati quelli di voler descrivere la variabilità di presentazione clinica dei pazienti affetti da tubercolosi del distretto testa-collo, durante la cui valutazione ci si scontra con notevoli difficoltà diagnostiche, e stimare la risposta di questi pazienti al trattamento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
0
3
0
4
Order By: Relevance
“…[ 13 ] Cervical lymph nodes are the most commonly studied site probably due to ease of approachability. [ 13 14 15 16 17 18 19 ] Similarly, abdominal TB has been studied separately in some studies, however, the number of lymph nodes included in the studies is few, with predominant cases being peritoneal and luminal TB. [ 20 21 22 23 ] Moreover, to the best of our knowledge, there are no comparative studies evaluating the cervical and abdominal lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13 ] Cervical lymph nodes are the most commonly studied site probably due to ease of approachability. [ 13 14 15 16 17 18 19 ] Similarly, abdominal TB has been studied separately in some studies, however, the number of lymph nodes included in the studies is few, with predominant cases being peritoneal and luminal TB. [ 20 21 22 23 ] Moreover, to the best of our knowledge, there are no comparative studies evaluating the cervical and abdominal lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with most other studies that have reported that most patients present within the second or third decade. [ 14 15 16 17 18 19 22 ] However, some studies show presentation in the higher age groups with a mean age of 39.2 years and 59.5 years. [ 13 20 ] Female preponderance was noted in our study with a male to female ratio of 1: 1.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…По данным литературы, частота выявления туберкулеза головы и шеи составляет 10% [2], при этом наиболее распространенное внелегочное поражение -туберкулезный лимфаденит, встречающийся от 73,3 [2] до 81,25% [3]. Говоря о поражении ЛОР-органов у больных туберкулезом (по данным исследований, как ретроспективных, так и проспективных), чаще приводят сравнительные данные туберкулеза той или иной ЛОРлокализации, и все единодушно отдают пальму первенства туберкулезу гортани (от 14,5 [2] до 15-37% [4]). В большинстве случаев туберкулез сочетается с поражением легких, но может быть и первичным очагом инфекции (19% [4]) или протекать изолированно без поражения легких (41,7%) [5].…”
Section: Introductionunclassified
“…Говоря о поражении ЛОР-органов у больных туберкулезом (по данным исследований, как ретроспективных, так и проспективных), чаще приводят сравнительные данные туберкулеза той или иной ЛОРлокализации, и все единодушно отдают пальму первенства туберкулезу гортани (от 14,5 [2] до 15-37% [4]). В большинстве случаев туберкулез сочетается с поражением легких, но может быть и первичным очагом инфекции (19% [4]) или протекать изолированно без поражения легких (41,7%) [5]. Согласно литературным источникам [3][4][5] в последние годы случаи туберкулеза гортани редки и единичны, но авторы единодушно отмечают, что изменились его клинические проявления в связи с широким применением антибиотиков и кортикостероидов: одинофагия перестала быть ведущей жалобой, уступив охриплости, при сохранении системных проявлений (лихорадка, потеря веса, ночная потливость) [5].…”
Section: Introductionunclassified